An Empirical Analysis of the Relationship among Foreign Direct Investment, Gross Domestic Product, CO2 Emissions, Renewable Energy Contribution in the context of the Environmental Kuznets Curve and Pollution Haven Hypothesis Regarding Turkey (European Journal of Formal Sciences and Engineering, 2020)
This study examines the relationships between GDP per capita, CO2 emission, Renewable Energy Contribution (REC) and Foreign Direct Investment (FDI) and evaluates the Environmental Kuznets Curve (EKC) and Pollution Haven Hypothesis (PHH) for Turkey. The EKC theory says that with increase in income per capita the pollution also increases but in a turning point when nation become richer pollution starts to decrease according to stringency of environmental regulations and implying advanced green technologies due to requirement of nation. In another hand the PHH assume that due to stringency of environmental regulations and high taxes the production become more expensive in developed countries, thus those dirty industries shifts from environmentally stricter developed countries to poor regulated developing countries. The aim of this study to analyze and investigate: which theory (EKC or PHH) does exist in Turkish economy and does FDI has positive impact on sustainable development. The time series datasets (FDI, GDP, CO2 and REC) , those were obtained from World Bank database, which covers the time period 1970-2014 were utilized in employed statistical models as the ADF Unit Root, Philips – Perron, Johansen co-integration, and the Granger Causality tests, to accomplish the empirical part of the paper. Based on the empirical results, it was approved that there wasn`t existence of the EKC theory in Turkish economy. But according to obtained empirical results it was affirmed that there was the presence of the PHH theory in Turkish economy which means the FDI has a negative impact on sustainable development of Turkish economy. Thus, the developed countries with stricter environmental regulations (mostly from Europe) relocate their heavily polluted dirty industries to Turkish economy.
Keywords: Foreign Direct Investment, CO2 Emissions, Gross Domestic Product, Renewable Energy Contribution, Environmental Kuznets Curve, Pollution Haven Hypothesis, ADF and Philips-Perron Unit root tests, Johansen Co-integration test, Granger Causality test